2014
DOI: 10.3109/10715762.2014.930455
|View full text |Cite
|
Sign up to set email alerts
|

17α-Estradiol down-regulates glutathione synthesis in serum deprived PC-12 cells

Abstract: During the last decades it has been shown that estrogen may have neuroprotective functions in the CNS. However, we have previously reported that pretreatment with estradiol abolishes its protection of cultured cerebellar granule neurons from glutamate-induced cell death due to down-regulation of endogenous glutathione. 17α-Estradiol is considered a hormonally inactive isomer of 17β-estradiol still containing its antioxidant potential. Here, we demonstrate that 17α-estradiol enhanced serum deprivation-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 183 publications
(243 reference statements)
0
6
0
Order By: Relevance
“…One of the estradiol-derivatives, E-3py, also reduced GCL activity at 1 nM. Literature findings suggest that estradiols elicit their neuroprotection is an ER-mediated [269], [270] manner, but previous findings in our own group suggest that PC12s do not express the classical ERs [271]. As the Nrf2-mediated p38 MATK pathway is implicated in the regulation of GSH, we evaluated the effects of the test compounds in the expression levels of these proteins, and found that only 2ME-11f-db increased levels of Nrf2, and this at 10 µM concentration, whereas levels of p38 were increased by 17αE, only at 10 µM.…”
Section: Estrogens As Neuroprotectantsmentioning
confidence: 64%
“…One of the estradiol-derivatives, E-3py, also reduced GCL activity at 1 nM. Literature findings suggest that estradiols elicit their neuroprotection is an ER-mediated [269], [270] manner, but previous findings in our own group suggest that PC12s do not express the classical ERs [271]. As the Nrf2-mediated p38 MATK pathway is implicated in the regulation of GSH, we evaluated the effects of the test compounds in the expression levels of these proteins, and found that only 2ME-11f-db increased levels of Nrf2, and this at 10 µM concentration, whereas levels of p38 were increased by 17αE, only at 10 µM.…”
Section: Estrogens As Neuroprotectantsmentioning
confidence: 64%
“…PC‐12 cells were cultivated as described previously , seeded at a density of 7.0 × 10 4 cells/ml and exposed after transfection on DIV1 to 0.1 μ m DEX, 1 μ m mifepristone, 0.1 μ m DEX + 1 μ m mifepristone, or ethanol 0.01‰.…”
Section: Methodsmentioning
confidence: 99%
“…The quality of ANDA's ability to quantify neuronal differentiation metrics was assessed using outlines of identified structures in freshly plated and in vitro day 3 CGN cells (Figure 2), as well as freshly plated and differentiated PC12N (Supplementary Figure 2) and NT2N (Supplementary Figure 3). Details of the cultivation of these three cell types are described in supplementary information [18,33]. To obtain phase contrast images of the cells we used the live-cell imaging platforms IncuCyte® ZOOM for the CGN and PC12N cells, and IncuCyte® S3 for the NT2N cells (Supplementary methods).…”
Section: Qualitative Measurement Assessmentmentioning
confidence: 99%